GAP Arthroplasty Versus Interpositional Arthropasty in the management of Temporaomandibular Joint Ankylosis - Ansari, Shuja Riaz; Khattak, Saddique Aslam; Iqbal, Shaheed; Nishtar, Sadia (Journal of Postgraduate Medical Institute, 2011)
The study was aimed to compare the results of gap arthroplasty and interpositional arthroplasty in the treatment of temporomandibular joint ankylosis surgery with particular reference to the recurrence of ankylosis. A total of 30 patients with temporomandibular joints ankylosis, 19 unilateral and 11 bilateral (41 joints) were operated and included both male and female with age rnage from 3 - 40 years with at least 2 - 3 years of follow up. The interpositional arthroplasty is the treatent of choice in any type or stage of ankylosis regardless of the age and duration.